(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The aim of this study is to investigate the nature of the relationship between domestic savings and domestic investment, or rather the efficiency of domestic savings in financing development in Algeria, in order to explain this relationship, identify the challenges to investment, and finance and accelerate economic growth. The economic measurement methodology has estimated the relationship between the savings rate and the local investment rate in the Algerian economy. We have annual data for the period 1970-2014. One of the most important conclusions is that there is no relationship between savings and investment, nor even an integration between them. To illustrate this, the use of some statistical tools, as well as unit root tests, was required, and the rank of integration of each variable was determined separately. The two variables have been shown to be complementary to the first order. Thus, the combined integration test of the Engel-Granger method and the Johansen method was used, in addition to the use of the Granger method of causation, to verify a long-term relationship between savings and investment. There is a balanced relationship between these two variables during the study period. The explanation for this is highlighted in the nature of the national economy, which relies heavily on the hydrocarbons sector as a main source of national income and foreign exchange, the non-diversification of economic activity and the structure of exports and the weak absorptive capacity National R on the other. Algeria, which relies on saving without internal investment outlets, means that development will remain stagnant or slow because of the lack of building productive sources to meet local needs and export surplus, which means that this is not true. Therefore, the study recommended the need to diversify sources of national income by encouraging large investments in infrastructure and in the productive sector of goods and services if the national economy is to be compatible with developed economies, especially since Algeria is currently experiencing an unprecedented financial crisis.